2007
DOI: 10.1182/blood-2007-01-071068
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of pregnancy complications in patients with essential thrombocythemia carrying the JAK2 (617V>F) mutation

Abstract: Essential thrombocythemia (ET) may occur in women of childbearing age. To investigate the risk of pregnancy complications, we studied 103 pregnancies that occurred in 62 women with ET. The 2-tailed Fisher exact test showed that pregnancy outcome was independent from that of a previous pregnancy. The rate of live birth was 64%, and 51% of pregnancies were uneventful. Maternal complications occurred in 9%, while fetal complications occurred in 40% of pregnancies. The Mantel-Haenszel method showed that fetal loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
131
3
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(153 citation statements)
references
References 33 publications
8
131
3
11
Order By: Relevance
“…First-trimester spontaneous miscarriage rate in ET or PV (>30%) [79][80][81] is significantly higher than the 15% rate expected in the control population and does not appear to be influenced by specific treatment [79]. Late obstetric complications as well as maternal thrombohemorrhagic events are relatively infrequent and platelet count usually decreases substantially during the second and third trimesters [82].…”
Section: Management Of Low-risk Pv or Et In The Absence Of Extreme Tmentioning
confidence: 93%
“…First-trimester spontaneous miscarriage rate in ET or PV (>30%) [79][80][81] is significantly higher than the 15% rate expected in the control population and does not appear to be influenced by specific treatment [79]. Late obstetric complications as well as maternal thrombohemorrhagic events are relatively infrequent and platelet count usually decreases substantially during the second and third trimesters [82].…”
Section: Management Of Low-risk Pv or Et In The Absence Of Extreme Tmentioning
confidence: 93%
“…18 PCR was performed on a RotorGene 6000TM real-time analyzer on a 100-well Gene Disk (Corbett Life Sciences, Mortlake, NSW, Australia) in two separate tubes for normal and mutated alleles. In all, 40 nanograms of genomic DNA were amplified in a 40-cycle PCR at an annealing temperature of 55 1C.…”
Section: Jak2 Mutational Analysismentioning
confidence: 99%
“…61 Interestingly, a recent study showed that JAK2 V617F is an independent predictor of pregnancy complications and that aspirin did not prevent complications in mutated patients and appear to worsen outcome in patients without the mutation. 62 Our management of pregnancy in MPNs is summarized in Table 5.…”
Section: Spotlightmentioning
confidence: 99%